Low-Dose Busulfan Reduces Human CD34(+) Cell Doses Required for Engraftment in c-kit Mutant Immunodeficient Mice - Leonard, Alexis (Mol Ther Methods Clin Dev, 2019)
Humanized animal models are central to efforts aimed at improving hematopoietic stem cell (HSC) transplantation with or without genetic modification. Human cell engraftment is feasible in immunodeficient mice; however, high HSC doses and conditioning limit broad use of xenograft models. We assessed human CD45(+) chimerism after transplanting varying doses of human CD34(+) HSCs (2 × 10(5) to 2 × 10(6) cells/mouse) with or without busulfan (BU) pretransplant conditioning in c-kit mutant mice that do not require conditioning (non-obese diabetic [NOD]/B6/severe combined immunodeficiency [SCID]/ interleukin-2 receptor gamma chain null (IL-2rγ(−/−)) Kit(W41/W41) [NBSGW]). We then tested a range of BU (5–37.5 mg/kg) using 2 × 10(5) human CD34(+) cells. Glycophorin-A erythrocyte chimerism was assessed after murine macrophage depletion using clodronate liposomes. We demonstrated successful long-term engraftment of human CD34(+) cells at all cell doses in this model, and equivalent engraftment using 10-fold less CD34(+) cells with the addition of BU conditioning. Low-dose BU (10 mg/kg) was sufficient to allow human engraftment using 2 × 10(5) CD34(+) cells, whereas higher doses (≥37.5 mg/kg) were toxic. NBSGW mice support human erythropoiesis in the bone marrow; however, murine macrophage depletion provided only minimal and transient increases in peripheral blood human erythrocytes. Our xenograft model is therefore useful in HSC gene therapy and genome-editing studies, especially for modeling in disorders, such as sickle cell disease, where access to HSCs is limited.